2001
DOI: 10.1007/pl00007252
|View full text |Cite
|
Sign up to set email alerts
|

The Decomposition Dimension of Graphs

Abstract: For an ordered k-decomposition D fG 1 ; G 2 ; . . . ; G k g of a connected graph G and an edge e of G, the D-representation of e is the k-tuple rejD de; G 1 ; de; G 2 ; . . . ; de; G k , where de; G i is the distance from e to G i . A decomposition D is resolving if every two distinct edges of G have distinct representations. The minimum k for which G has a resolving k-decomposition is its decomposition dimension dec(G). It is shown that for every two positive integers k and n ! 2, there exists a tree T of ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…The decomposition dimensions of trees that are not paths have been studied in [7,26], where bounds for them have been determined. However, there is no general formula for the decomposition dimension of a tree that is not a path.…”
Section: Connected Resolving Decompositions a Resolving Decompositionmentioning
confidence: 99%
“…The decomposition dimensions of trees that are not paths have been studied in [7,26], where bounds for them have been determined. However, there is no general formula for the decomposition dimension of a tree that is not a path.…”
Section: Connected Resolving Decompositions a Resolving Decompositionmentioning
confidence: 99%
“…For the complete graph K n , the trivial lower bound resulting from (1) is about 2 lg n−lg lg n. In [2], it was proved that dec(K n ) ≤ (2n+5)/3 for n ≥ 3. This bound was improved by Nakamigawa [8] …”
Section: Complete Graphs and Union-free Families Of Setsmentioning
confidence: 99%
“…A decomposition is distinguishing if the resulting distance vectors for edges are distinct. Chartrand, Erwin, Raines, and Zhang [2] defined the decomposition dimension dec(G) to be the minimum number of colors in a a distinguishing decomposition of G. Since every distance vector has exactly one 0 and the remaining entries are at most d + 1 when G has diameter d, they observed that (1) dec(G) = k implies |E(G)| ≤ k(d + 1) k−1 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations